Optimized Load-Scheduling Algorithm for CubeSat's Electric Power System Management Considering Communication Link - Bayan Hussein (16904856) (2023)
CubeSats have been gaining significant interest as a cost-effective solution that can be built with low power requirements for different mission types. The most critical subsystem in CubeSats is the electrical power subsystem (EPS), which provides the required power to operate the remaining subsystems. This article presents an approach for optimizing load management and scheduling in CubeSat applications to ensure optimal coordination between the load demand, power generation, and energy storage while maintaining communication's quality of service requirements, namely the data rate and bit error rate (BER). The loads are divided into four types based on their priority. The load types are time-modulated, magnitude-modulated, time-and-magnitude-modulated, and fixed. An optimization problem is formulated with data rate and BER in the cost function while maintaining energy and power constraints. Multiple cases are investigated with different mission requirements. The solution obtained shows that the proposed scheduling algorithm meets the communication system's requirements while conserving power and energy resources. Other Information Published in: IEEE Transactions on Aerospace and Electronic Systems License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/taes.2023.3290547